Validate the Content and Authenticity of the Sender for Text Messages Using QR Code (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
In light of the information revolution taking place in the modern world, therefore it becomes necessary and important to save this electronic messages. So we offered this technique to ensure the safety of the content of the messages and authenticity of the sender through  networks communication by converting the message's symbols to numbers , each one of this symbols (letters, numbers, symbols) will converted into three digits, the first digit represents the ASCII code of the symbol, the second digit represents the frequency of this symbol in the message (the number of times this symbol is appear in the message), and the third digit represents the total number of the locations of the symbol (calculates the symbol location from the first symbol in the message to this symbol itself and blanks also calculated too) .The digital signature of the sender will converted to numbers like the symbols of message we explained it before, and this numbers of the digital signature will gathering together to produce three numbers only, this number will gathering with each numbers of the message's symbols, the final  numbers will converted to QR Code, the QR Code will placed with the message and sent to the recipient. The recipient returns the steps of the sender (produce QR Code from the received message) and compared it the received QR Codes, if it is match or not. The recipient will ensure that the content is secure, and confirms the authenticity of the sender.